Utilization of Colocynth (Handal) Seeds Oil as a Lubricating Base Oil - Abdelrahman, Maha A. A.; Yassin, Atif A. A.; Abdou, Abdelnasir M. (Gezira Journal of Engineering and Applied Sciences, 2018)
This study investigated the use of Colocynth seeds oil as lubricating base oil. The Colocynth seeds were collected from Eastern Gezira and Western Kordofan. Viscosity index is 162 and 164; Flash point is 292 o C and 288 o C for Eastern Gezira and Western Kordofan samples, respectively. The pour point is -3 o C for both samples. At 40 o C, the kinematics viscosity is 34.37 cSt and 32.69 cSt, and at 100 o C is 8.00 cSt and 7.77 cSt for Eastern Gezira and Western Kordofan samples, respectively. The study suggested that the Colocynth seeds oil is a suitable base fluid to produce lubricants .